Impulsive Choice in Mice Lacking Paternal Expression of Grb10 Suggests Intragenomic Conflict in Behavior. Issue 1 (21st March 2018) - Dent, Claire L; Humby, Trevor; Lewis, Katie; Ward, Andrew; Fischer-Colbrie, Reiner; Wilkinson, Lawrence S; Wilkins, Jon F; Isles, Anthony R
Abstract: The imprinted gene Grb10 is expressed in the brain from the paternal copy only. Here, Dent et al. show that paternal Grb10 regulates impulsive choices, i.e. whether an animal chooses a smaller food reward... Imprinted genes are expressed from one parental allele only as a consequence of epigenetic events that take place in the mammalian germ line and are thought to have evolved through intragenomic conflict between parental alleles. We demonstrate, for the first time, oppositional effects of imprinted genes on brain and behavior. Specifically, we show that mice lacking paternal Grb10 make fewer impulsive choices, with no dissociable effects on a separate measure of impulsive action. Taken together with previous work showing that mice lacking maternal Nesp55 make more impulsive choices, this suggests that impulsive choice behavior is a substrate for the action of genomic imprinting. Moreover, the contrasting effect of these two genes suggests that impulsive choices are subject to intragenomic conflict and that maternal and paternal interests pull this behavior in opposite directions. Finally, these data may also indicate that an imbalance in expression of imprinted genes contributes to pathological conditions such as gambling and drug addiction, where impulsive behavior becomes maladaptive.